El control interno y su impacto en la gestión financiera de la Empresa NMD S.A. - Constante Espinoza, Nikole Maribe (2024)
The degree project entitled "Internal control and its impact on the financial management of the company NMD S.A." focuses on analyzing how an effective internal control can improve the financial management of a company dedicated to the rental and sale of medical offices. The research focuses on the need to implement an internal control system due to the current problems faced by the company, such as inconsistencies and accounting errors, difficulties in obtaining accurate financial information, and the risk of misuse of funds. The problem is stated and formulated, identifying the lack of an adequate internal control system as the main cause of the financial problems. Both general and specific objectives are established, focused on developing and implementing an internal control system that optimizes financial management.......